Anti-citrullinated histone monoclonal antibody CIT-013, a dual action therapeutic for neutrophil extracellular trap-associated autoimmune diseases - Maarten van der Linden; Sangeeta Kumari; Daphne Montizaan; Stephanie van Dalen; Annemarie Kip; Martyn Foster; Inge Reinieren-Beeren; Elsa Neubert; Luise Erpenbeck; Kelsy Waaijenberg; Tirza Bruurmijn; Rezie te Poele; et al. (Taylor & Francis Group, 2023)
ABSTRACTNeutrophil extracellular traps (NETs) contribute to the pathophysiology of multiple inflammatory and autoimmune diseases. Targeting the NETosis pathway has demonstrated significant therapeutic potency in various disease models. Here, we describe a first-in-class monoclonal antibody (CIT-013) with high affinity for citrullinated histones H2A and H4, which inhibits NETosis and reduces tissue NET burden in vivo with significant anti-inflammatory consequences. We provide a detailed understanding of the epitope selectivity of CIT-013. Detection of CIT-013 epitopes in rheumatoid arthritis (RA) synovium provides evidence that RA is an autoimmune disease with excessive citrullinated NETs that can be targeted by CIT-013. We show that CIT-013 acts upon the final stage of NETosis, binding to its chromatin epitopes when plasma membrane integrity is compromised to prevent NET release. Bivalency of CIT-013 is necessary for NETosis inhibition. In addition, we show that CIT-013 binding to NETs and netting neutrophils enhance their phagocytosis by macrophages in an Fc-dependent manner. This is confirmed using a murine neutrophilic airway inflammation model where a mouse variant of CIT-013 reduced tissue NET burden with significant anti-inflammatory consequences. CIT-013's therapeutic activity provides new insights for the development of NET antagonists and indicates the importance of a new emerging therapy for NET-driven diseases with unmet therapeutic needs.